2016
DOI: 10.1111/aje.12364
|View full text |Cite
|
Sign up to set email alerts
|

Response of riparian plant communities to distance from surface water in the Okavango Delta, Botswana

Abstract: The objective of this study was to determine the influence of distance from surface water on riparian woodland communities in the Okavango Delta. Vegetation sampling was conducted in seven sites within the Okavango Delta in 20 m × 10 m belted plots placed perpendicular to the river bank. The plots were placed at 0–10 m, 10–20 m, 20–30 m, 30–40 m and 40–50 m distance classes increasing away from the river bank. Tree height, basal area, species richness, canopy cover and diversity were determined for each distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
8
1
Order By: Relevance
“…We found that plant species diversity in riparian woodlands along the middle and lower reaches of the Yellow River in China varied with distance from the river. Our results are inconsistent with those from Lite et al [34], Zenner et al [35], and Tsheboeng et al [42], who found no overall variation in species richness as a function of distance from river. We expect that our results may differ due to the unique geomorphology of the Yellow River.…”
Section: Variation In Plant Species Diversity Along Lateralcontrasting
confidence: 99%
See 1 more Smart Citation
“…We found that plant species diversity in riparian woodlands along the middle and lower reaches of the Yellow River in China varied with distance from the river. Our results are inconsistent with those from Lite et al [34], Zenner et al [35], and Tsheboeng et al [42], who found no overall variation in species richness as a function of distance from river. We expect that our results may differ due to the unique geomorphology of the Yellow River.…”
Section: Variation In Plant Species Diversity Along Lateralcontrasting
confidence: 99%
“…However, with regard to Pielou's evenness (J) and Simpson's diversity (D), there was no significant difference among the four subzones. On one hand, this suggests that distance from the river may either have no significant impact on the distribution of species inhabiting the riparian zone, or that they have a significant influence on species composition alone [42]. On the other hand, there might be other environmental gradients [9,11,43] or anthropogenic disturbances [14,17,18] that control the characteristics of species evenness or diversity in this ecosystem that were not included in the present study.…”
Section: Variation In Plant Species Diversity Along Lateralmentioning
confidence: 87%
“…The recent study by Tsheboeng et al (2017) investigated the influence of distance from surface water on riparian plant species composition and distribution in the Okavango Delta. However, that study was limited as it did not study response of plant species to distance from surface water in different sites.…”
Section: Introductionmentioning
confidence: 99%
“…This difference could suggest that not all species are favoured by the prevailing environmental conditions in the distal regions of the Delta. The Syzygium cordatum-Phoenix reclinata woodland community is associated with frequent flooding conditions, which are absent in the riparian zone of the distal regions of the Okavango Delta (Tsheboeng et al 2016b), hence, its exclusion along the Thamakalane River, which is a seasonally flooded area. Croton megalobotrys was a dominant species along the Thamalakane River and the upstream regions of the Delta.…”
Section: Discussionmentioning
confidence: 99%